PENGARUH PENYAJIAN LAPORAN KEUANGAN DAERAH, AKSESIBILITAS LAPORAN KEUANGAN DAN SISTEM PENGENDALIAN INTERN TERHADAP AKUNTABILITAS PENGELOLAAN KEUANGAN DAERAH - Ni Luh Wulan Artini; I Putu Deddy Samtika Putra (Hita Akuntansi dan Keuangan, 2020)
The purpose of this study was to examine the effect of Regional Financial Report Presentation, Financial Statement Accessibility and Internal Control Systems on Regional Financial Management Accountability (Empirical Study at the Regional Financial and Revenue Management Agency (BPKPD) Klungkung Regency). This research was conducted at BPKPD Klungkung Regency with a total sample of 57 employees, with a purposive sampling method. The type of data used is primary data. The data was collected by using questionnaires and data processing using multiple linear regression analysis. The results of this study indicate that (a) the regional financial statement presentation variables affect the accountability of regional financial management. (b) the variable of financial report accessibility has no effect on the accountability of regional financial management (c) the variable of the internal control system has no effect on the accountability of regional financial management.